Fiqh Kontemporer dalam Pengaturan Etika Media Sosial Bagi Umat Muslim - Sahil, Irdlon (Journal of Economic and Islamic Research, 2024)
The digital era has transformed human interaction and communication, with social media emerging as a primary platform for sharing information and fostering global dialogue. However, social media presents ethical challenges, particularly for Muslims striving to adhere to Islamic principles. This study examines the role of contemporary fiqh in establishing ethical guidelines for social media usage among Muslims. Utilizing a qualitative approach, data were collected through literature reviews, interviews with Islamic scholars and social media users, and participatory observations. The findings highlight key fiqh principles—truthfulness, justice, privacy preservation, and avoidance of slander and gossip—as essential for responsible social media engagement. Challenges identified include the spread of misinformation, hate speech, and privacy violations. Fatwas from institutions like the Indonesian Ulema Council provide practical guidelines, emphasizing ethical communication and respect for others' rights. The study underscores the importance of education on digital ethics rooted in Islamic values to address the evolving ethical dilemmas of the digital age. Recommendations include broader dissemination of fiqh-based ethical frameworks to promote responsible and value-driven social media usage among Muslim communities.